UPACARA PERAN DUA KERAJAAN DALAM MEMPERTAHANKAN MALABOT TUMPE/TUMBE DI SULAWESI TENGAH - Nurhani Nurhani; Wa Ode Sifatu (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2018)
The purpose of this study was to determine the role of the two kingdoms in maintaining the implementation of the Malabot tumpe / Tumbe ceremony, as well as to find out some things that hindered the Banggai community's participation in the ceremony. This study uses Radcliffe Brown's theory; thinking about structural functionalism. The results showed that the Banggai Kingdom and the Matindok Kingdom had sought legal legitimacy over the ownership of customary land in the area precisely in the Bakiriang forest so that the maleo bird was well preserved in the area. This condition has implications for the survival of the tumpe / tumbe ceremony in Banggai. The Matindok kingdom delivers maleo eggs to the Banggai kingdom and then the Banggai kingdom picks up the eggs and shares them with the rightful ones. However, the inclusion of outside culture, the existence of jobs, the existence of social jealousy, and a lack of understanding of the culture itself resulted in a decline in the participation of the Banggai royal community in the implementation of the malabot tumbe ceremony. The relationship between the kingdom of Banggai and the kingdom of Matindok in maintaining the ceremony of Malabot tumpe / Tumbe is very close and has mutual attachments to each other because the ceremony of Malabot Tumpe / Tumbe is an ancestral cultural heritage that must be maintained and preserved by the two kingdoms. Keywords: ceremony, role, kingdoms, malabot tumpe/tumbe